2002
DOI: 10.1002/elps.200290026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of benzo[a]pyrene diol epoxide‐DNA adducts by capillary zone electrophoresis‐ electrospray ionization‐mass spectrometry in conjunction with sample stacking

Abstract: Benzo[a]pyrene diol epoxide (BPDE) was reacted in vitro with (2'-deoxy)nucleotides and with calf thymus DNA. The modified DNA was enzymatically hydrolyzed to the 5'-monophosphate nucleotides using deoxyribonuclease I (DNA-ase I), nuclease P1 and snake venom phosphodiesterase (SVP). Most of the unmodified nucleotides were removed using solid phase extraction (SPE) in a polystyrene divinylbenzene copolymer. Three adducts could be detected and identified using capillary zone electrophoresis(negative)-ion electros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…Benzo[a]pyrene (B[a]P) is a representative of carcinogenic PAH. It is metabolized in vivo to an ultimate carcinogen, anti-benzo [a]pyrene diol epoxide (BPDE), which may bind to an exocylic amine group at N 2 -deoxyguanosine (dG) or N 6 -deoxyadenosine(dA) in DNA [8]. It is possible to form four stereoisomers of anti-BPDE-N 2 dG and four stereoisomers of anti-BPDE-N 6 dA, derived from the reaction of (±)-anti-BPDE with DNA [9].…”
Section: Introductionmentioning
confidence: 99%
“…Benzo[a]pyrene (B[a]P) is a representative of carcinogenic PAH. It is metabolized in vivo to an ultimate carcinogen, anti-benzo [a]pyrene diol epoxide (BPDE), which may bind to an exocylic amine group at N 2 -deoxyguanosine (dG) or N 6 -deoxyadenosine(dA) in DNA [8]. It is possible to form four stereoisomers of anti-BPDE-N 2 dG and four stereoisomers of anti-BPDE-N 6 dA, derived from the reaction of (±)-anti-BPDE with DNA [9].…”
Section: Introductionmentioning
confidence: 99%
“…Using CZE-MS to analyse 2 0 -deoxynucleoside 5 0 -monophophates, Willems et al identified the formation of adducts with exocyclic -NH 2 groups of guanine, adenine and cytosine following the reaction of benzo[a]pyrene diol epoxide with calf thymus DNA. The authors used an online sample stacking technique for the pre-concentration of the negatively charged adducts and removal of sample buffer (196). A similar approach was used by Barry et al to analyse enzymatically hydrolysed calf thymus DNA treated with benzo[a]pyrene diol epoxide for which the authors noted the presence of an adducted thymidine-guanine dinucleotide in addition to a 2 0 -deoxyguanosine 5 0 -monophosphate adduct of benzo[a]pyrene diol epoxide (197).…”
Section: Analytical Developmentsmentioning
confidence: 99%
“…Because of the nature of the stacking process, the method lends itself particularly well to the analysis of negatively charged species and, as a consequence, to the analysis of oligonucleotides [34,36,37,40]. This sample stacking technique has already been used with success by our research group and the groups of Vouros et al for the analysis of deoxynucleotide DNA adducts of phenyl glycidyl ethers [40] and benzo[a]pyrene [37,41] and the analysis of oligonucleotides [10] by CZE coupled to ESI-MS.…”
Section: Introductionmentioning
confidence: 93%
“…Sample stacking was necessary to preconcentrate the oligonucleotide samples and was performed as described earlier with minor modifications [41]. The voltage of reversed polarity was tested in the range of 27 to 230 kV, resulting in the best signal response when 220 kV was used.…”
Section: Stacking Proceduresmentioning
confidence: 99%